(untitled) (TEST Trento Student Law Review, 2024)
Normally, mafia-style organized crime assumes, in our minds, a well-defined image given by the traditional representations that are still shown to us in films today. But is this still the case today? It is clear that things are changing, that it is increasingly difficult to see those classic forms of organized crime in a world so different from that of 40 years ago. This is because the mafias are differentiating, they are taking on different forms, they are increasingly transparent from a double point of view: it is difficult to trace their movements in the commission of those crimes that are part of a single criminal design, just as it is difficult to trace those classic forms of intimidation because the communications between members of the association, but also with outsiders, they are different. This transparency can only be explained in one way: technology, new forms of communication, have pushed this change to the point of leading the mafias to conform to our behavior. What makes criminal activity go unnoticed are the increasing difficulties in differentiating the behaviors that are now considered habitual and those that, on the other hand, are typical behaviors of mafia associations. It is now clear that a change, a turning point, a moment of reflection is absolutely necessary to be able to look beyond what we are used to doing.